Species-specific physiological status in seabirds: insights from integrating oxidative stress measurements and biologging - Koyama, Shiho; Mizutani, Yuichi; Goto, Yusuke; Yoda, Ken (Frontiers in Physiology, 2025)
Understanding the relationship between behavior and physiological state, as well as species differences in physiological responses, is key to identifying the behavioral and physiological adaptations necessary for wild animals to avoid physiological deterioration, thereby enhancing their survival and fitness. A commonly used measure of physiological condition is oxidative stress, which results from an imbalance between oxidative damage—often exacerbated by respiration during exercise and indicative of physical harm—and antioxidant capacity, which reflects the organism’s ability to recover from such damage. Despite its importance, oxidative stress has rarely been linked to behavior, such as foraging, leaving this relationship underexplored. In this study, we focused on two seabird species, black-tailed gulls (Larus crassirostris) and streaked shearwaters (Calonectris leucomelas), which are similar in body size and primarily forage on the same prey species but differ in traits such as habitat, flight style, and physiological function. We recorded the trajectories of these birds for approximately 1 week using biologging and measured their plasma oxidative stress. We found that oxidative stress in black-tailed gulls was higher than that in streaked shearwaters, suggesting that species differences in life histories, habitats, and physiological function may be related to long-term oxidative stress. However, over a 1-week timescale, there were no significant species differences in changes in oxidative stress, suggesting that behavioral differences between the two species might not necessarily lead to species-specific oxidative stress responses in the short term. Additionally, no consistent relationship was found between changes in oxidative stress of the two species and their behavioral metrics in most years, suggesting that this relationship may vary depending on yearly environmental fluctuations. Based on our findings, we encourage future studies that would explore and integrate the interactions between marine environments, behavior, and oxidative stress of different bird species to clarify the contribution of specific foraging behaviors to either the deterioration or recovery of physiological conditions, and the varying effect of environmental conditions on these relationships.